2017
DOI: 10.3389/fnana.2017.00029
|View full text |Cite
|
Sign up to set email alerts
|

Glial Cell Line-Derived Neurotrophic Factor Gene Delivery in Parkinson's Disease: A Delicate Balance between Neuroprotection, Trophic Effects, and Unwanted Compensatory Mechanisms

Abstract: Glial cell line-derived neurotrophic factor (GDNF) and Neurturin (NRTN) bind to a receptor complex consisting of a member of the GDNF family receptor (GFR)-α and the Ret tyrosine kinase. Both factors were shown to protect nigro-striatal dopaminergic neurons and reduce motor symptoms when applied terminally in toxin-induced Parkinson's disease (PD) models. However, clinical trials based on intraputaminal GDNF protein administration or recombinant adeno-associated virus (rAAV)-mediated NRTN gene delivery have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 119 publications
1
47
0
Order By: Relevance
“…A third option, the intracerebral gene delivery using the stereotaxic injection of viral vectors to allow GDNF to reach its target structure in the basal ganglia, remains a major challenge. Further studies are warranted to overcome these obstacles of passing the BBB in clinical studies and to finally compass gene delivery via viral vectors …”
Section: Current Developments: Neuroprotection and Neurorestorationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A third option, the intracerebral gene delivery using the stereotaxic injection of viral vectors to allow GDNF to reach its target structure in the basal ganglia, remains a major challenge. Further studies are warranted to overcome these obstacles of passing the BBB in clinical studies and to finally compass gene delivery via viral vectors …”
Section: Current Developments: Neuroprotection and Neurorestorationsmentioning
confidence: 99%
“…Further studies are warranted to overcome these obstacles of passing the BBB in clinical studies and to finally compass gene delivery via viral vectors. 80,81 Another approach to enhance compensatory and regenerative mechanisms in the brain is the propagation of axonal growth. The protein kinase Akt/master kinase mammalian has been modulated.…”
Section: Neurotrophic Factorsmentioning
confidence: 99%
“…PD, which is well known as one of the most common progressive neurodegenerative diseases, is characterized by the loss or death of nigral dopaminergic neurons. Many previous studies on preclinical models of PD and clinical trials have demonstrated the salutary impact of GDNF on dopamine neuron survival and nerve regeneration. Based on these studies, the overexpression of GDNF genes in neurons can potentially slow neurodegenerative disease progression.…”
Section: Therapeutic Genes For Cns Diseasesmentioning
confidence: 99%
“…have demonstrated the salutary impact of GDNF on dopamine neuron survival and nerve regeneration 27,28 . Based on these studies, the overexpression of GDNF genes in neurons can potentially slow neurodegenerative disease progression.…”
Section: Many Previous Studies On Preclinical Models Of Pd and Clinicmentioning
confidence: 99%
“…Many clinical trials have commenced looking at the use of rAAV for treating a variety of conditions including but not limited to Pompe disease, cystic fibrosis, Parkinson's disease, muscular dystrophy, α-1 antitrypsin deficiency, and hemophilia [24][25][26][27][28]. Europe has even approved a rAAV drug manufactured under the name Glybera, which is the first gene therapy, to treat a very rare disease called lipoprotein lipase deficiency [29].…”
Section: Recombinant Adeno-associated Virus Vectors (Raav)mentioning
confidence: 99%